Methamphetamine Exposure in Adolescent Impairs Memory of Mice in Adulthood Accompanied by Changes in Neuroplasticity in the Dorsal Hippocampus - Liang, Min; Zhu, Li; Wang, Rui; Su, Hang; Ma, Dongliang; Wang, Hongyan; Chen, Teng (Frontiers in Cellular Neuroscience, 2022)
Methamphetamine (METH) has been shown to alter learning and memory by affecting the neuroplasticity of the dorsal hippocampus, a key structure that undergoes extensive remodeling during adolescence. In the present study, we investigated whether mid-to-late adolescent exposure to METH leads to long-lasting memory impairment. To do this, adolescents (postnatal days 35-48) were exposed to different doses of METH for 14 days and then evaluated by the Morris water maze (MWM), new object recognition test (NORT), and the Y-maze, to investigate the learning and memory ability of mice in their adolescence and adulthood, respectively. We also detected the mRNA levels of genes associated with neuroplasticity in the dorsal hippocampus. The synaptic ultrastructure and the number of neurons and astrocytes in the dorsal hippocampus were also determined by transmission electron microscopy (TEM) and immunofluorescence (IF). Exposure to METH in mid-to-late adolescence impaired spatial memory retrieval ability and the long-term recognition memory of mice in their adulthood, but not in their adolescence. Of note, the impairment of memory capacity in adulthood was accompanied by molecular and structural changes in synapses in the dorsal hippocampus. Our results indicate that mice exposed to METH in mid-to-late adolescence have impaired memory ability in their adulthood; this may be the result of abnormal changes in the structural plasticity of the dorsal hippocampus; the causal relationship between changes in synaptic structural plasticity and memory impairment needs to be further confirmed. In summary, our study provides evidence for the detrimental consequences of adolescent addiction and the prevention of adolescent drug abuse.